Proximate analysis of selected marine fishes in Kuantan, Pahang - Mat Jusoh, Hanapi; MD Guzali, Ilyana Zakira (International Islamic University Malaysia, 2023)
Introduction: Marine fish is a good of protein and fatty acids. The nutrient compositions of fish vary due to many factors including different species, maturity of the fish and geographical regions. Hence, this study aimed to analyse proximate composition of four marine fish that commonly consumed by Malaysian, namely Silver Pomfret, Black Pomfret, Yellowstripe Scad and Yellowtail Scad. Methods: The proximate composition of moisture, protein, fat, and ash were measured according to method described by Association of Official Analytical Chemists (AOAC) 1990 with slight modifications. Data was analysed using Analysis of Variance (ANOVA), with a significance level used for all tests was at 95%. Results: There were no differences in the percentages of fat and protein among the selected fish except for ash and moisture contents. Silver Pomfret and Yellowstripe Scad had significantly higher moisture contents than Black Pomfret, Yellowtail Scad (p<0.05). Yellowstripe Scad exhibited the lowest ash content among the selected fish species, with a significant difference only when compared to Silver Pomfret (p<0.05). Conclusion: While there was no significant variation in protein and fat content, this study highlights the differences in moisture and ash composition among the four fish species. Future studies could further investigate the mineral contents present in the ash.